Comprehensive review of vascularized lymph node transfers for lymphedema: Outcomes and complications. Issue 2 (7th June 2016) - Scaglioni, Mario F.; Arvanitakis, Michael; Chen, Yen‐Chou; Giovanoli, Pietro; Chia‐Shen Yang, Johnson; Chang, Edward I.
Abstract : Introduction: Lymphedema remains a challenging clinical problem. A new field of lymphatic surgery using micro and super microsurgery techniques is a rapidly advancing field aimed to treat recalcitrant cases. The objective of this study was to evaluate outcomes and complications of vascularized lymph node transfer (VLNT). Several early preliminary studies have reported promising outcomes, but they are limited by small numbers, short follow‐up, and are inconsistent in addressing the origin and recipient site of the transferred lymph nodes as well as the donor site morbidity. Methods: A review of literature was conducted using PubMed‐MEDLINE, EMBASE for key words vascularized lymph node transfer (also autologous, lymph node transplant). Only human studies were included. Results: A total 24 studies encompassing 271 vascularized lymph node transfers were included. The inguinal nodes were the most commonly used donor site followed by the lateral thoracic lymph nodes. The lateral thoracic lymph nodes were the least effective and had the highest complication rates (27.5%) compared to other lymph node donor sites (inguinal: 10.3% and supraclavicular: 5.6%). Upper extremity lymphedema responded better compared to lower extremity (74.2 vs. 53.2%), but there was no difference in placing the lymph nodes more proximally versus distally on the extremity (proximal: 76.9% vs. distal: 80.4%). Conclusion: Vascularized lymph node transfer for lymphedema treatment is a promising operative technique showing beneficial results in early but also in advanced stage lymphedema. This physiologic surgical procedure should be included in a modern reconstructive concept for lymphedema treatment. © 2016 Wiley Periodicals, Inc. Microsurgery 38:222–229, 2018.